Ang Dumaracol ng Kalamianen Tagbanua ng hilagang Palawan isang panimulang paglalahad - Guieb, Eulalio R., III (Humanities Diliman, 2014)
This study is the first documentation of the long narrative song dumaracol of the Kalamianen Tagbanua of Northern Palawan on the islands bordering the towns of Taytay, El Nido, and Linapacan. The essay is the first in a multi-stage research that collects, records, documents, transcribes, translates into Filipino, and examines the said genre.